2014
DOI: 10.1016/j.molonc.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic expression of cancer/testis antigen SSX2 induces DNA damage and promotes genomic instability

Abstract: SSX cancer/testis antigens are frequently expressed in melanoma tumors and represent attractive targets for immunotherapy, but their role in melanoma tumorigenesis has remained elusive. Here, we investigated the cellular effects of SSX2 expression. In A375 melanoma cells, SSX2 expression resulted in an increased DNA content and enlargement of cell nuclei, suggestive of replication aberrations. The cells further displayed signs of DNA damage and genomic instability, associated with p53-mediated G1 cell cycle ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 30 publications
4
37
0
Order By: Relevance
“…The authors also showed that knockdown of SSX2 expression had a similar effect to the overexpressed constructs, with cell growth being diminished [27]. Therefore, based on these data, the authors concluded that melanoma appears dependent on an optimal level of SSX2 expression [27]. With these data in mind, we selected SSX4 as a representative of the SSX family for further investigation.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…The authors also showed that knockdown of SSX2 expression had a similar effect to the overexpressed constructs, with cell growth being diminished [27]. Therefore, based on these data, the authors concluded that melanoma appears dependent on an optimal level of SSX2 expression [27]. With these data in mind, we selected SSX4 as a representative of the SSX family for further investigation.…”
Section: Resultsmentioning
confidence: 97%
“…Strikingly, cell proliferation and migration were unaffected by the lack of SSX4 or SSX4B expression [26]. Furthermore, in A375 cells, induction of SSX2 expression using a lentiviral construct (above endogenous tumour levels) led to a reduction of cell viability and colony formation, and induced cell cycle G1 checkpoint arrest [27]. SSX2 expression was further found to induce DNA damage response which promoted genomic instability [27].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[19][20][21][22][23][24][25][26][27][28][29][30], including the fostering of genome instability, a driver of cancer evolution (24). However, given that the normal function of many CT genes in spermatogenesis is unknown, it remained unclear whether proteins that normally specifically orchestrate meiotic chromosome segregation events (such as interhomolog association/recombination and sister centromere monopolarity) contribute to maintenance and/or development/progression of cancers.…”
Section: Activation Of Meiotic Functions In Cancer Cellsmentioning
confidence: 99%